Pengaruh Terpaan Konten Artikel Pada Website dan Instagram Go Mandalika Terhadap Pengetahuan Wisatawan Tentang Pariwisata Kabupaten Lombok Tengah - Nugraha, Lalu Muhammad Rifqi; Kriyantono, Rachmat (Universitas Brawijaya, 2023)
The development of technology and communication is currently growing very rapidly. The use of communication in various fields has developed, one of which is in the field of tourism to carry out tourism promotion. The Central Lombok Regency Tourism and Culture Office has digital communication media in the form of a website and Instagram called Go Mandalika. The focus of this research is to see the effect of exposure to article content on the Go Mandalika website and Instagram on the level of tourist knowledge about tourism in Central Lombok Regency. This study uses explanatory quantitative methods using simple linear regression. This research was conducted by distributing questionnaires online (google form) via instagram, whatsApp, and kudata.id to 100 respondents. The research sampling technique used simple random sampling. The results of this study indicate that exposure to article content has a positive effect on the tourist knowledge variable by 59.6%. Based on data analysis in this study, Instagram is the digital media that has the most influence on the level of knowledge of tourists and also Instagram is more frequently visited to find information about tourism in Central Lombok Regency.